PENGEMBANGAN MEDIA E-MODUL INTERAKTIF BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS V SD 5 CENDONO - Muhalimah, Anisa; Sekar Dwi Ardianti; Fatikhatun Najikhah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to determine (1) the feasibility level of Augmented Reality-assisted E-Module media. (2) to know the practicality of interactive Augmented Reality-assisted E-Module media. The type of research method used is R&D (Research and Development) employing the ADDIE development model, which consists of 5 stages: analysis, design, implementation, and evaluation. The population of this study consists of 22 fifth-grade students at SD 5 Cendono. Based on the results of the development research of Augmented Reality-assisted E-Module to increase learning interest, media expert 1 received a percentage of 84% and was stated to be "very feasible." Media expert 2 received a percentage of 94% and was stated to be "very feasible." The results of the small group trial obtained a percentage of 88% and were stated to be "very feasible," and the results of the large group trial obtained a percentage of 85% and were stated to be "very feasible." From the results of the research, the development of interactive Augmented Reality-assisted E-Module media has the category of "very suitable" for use and to enhance students' learning interest.